Volatile element signatures in the mantles of Earth, Moon, and Mars: Core formation fingerprints from Bi, Cd, In, and Sn. (1st December 2017) - Righter, K.; Pando, K.; Marin, N.; Ross, D. K.; Righter, M.; Danielson, L.; Lapen, T. J.; Lee, C.
Abstract: Volatile element concentrations in planets are controlled by many factors such as precursor material composition, core formation, differentiation, magma ocean and magmatic degassing, and late accretionary processes. To better constrain the role of core formation, we report new experiments defining the effect of temperature, and metallic S and C content on the metal‐silicate partition coefficient (or D ( i ) metal/silicate) of the volatile siderophile elements (VSE) Bi, Cd, In, and Sn. Additionally, the effect of pressure on metal‐silicate partitioning between 1 and 3 GPa, and olivine‐melt partitioning at 1 GPa have been studied for Bi, Cd, In, Sn, As, Sb, and Ge. Temperature clearly causes a decrease in D ( i ) metal/silicate for all elements. Sulfur and C have a large influence on activity coefficients in metallic Fe liquids, with C causing a decrease in D ( i ) metal/silicate, and S causing an increase. Pressure has only a small effect on D (Cd), D (In), and D(Ge) metal/silicate. Depletions of Bi, Cd, In, and Sn in the terrestrial and Martian mantles are consistent with high PT core formation and metal‐silicate equilibrium at the high temperatures indicated by previous studies. A late Hadean matte would influence Bi the most, due to its high D (sulfide/silicate) ~2000, but segregation of a matte would only reduce the mantle Bi content by 50%; all other less chalcophile elements (e.g., Sn, In, and Cd) would be minimally affected. The lunar depletions of highly VSE require a combination of core formation and an additional depletion mechanism—most likely the Moon‐forming giant impact, or lunar magma ocean degassing.